2016
DOI: 10.1038/srep22515
|View full text |Cite
|
Sign up to set email alerts
|

Directly Predicting Water Quality Criteria from Physicochemical Properties of Transition Metals

Abstract: Transition metals are a group of elements widespread in aquatic environments that can be hazardous when concentrations exceeding threshold values. Due to insufficient data, criteria maximum concentrations (CMCs) of only seven transition metals for protecting aquatic life have been recommended by the USEPA. Hence, it is deemed necessary to develop empirical models for predicting the threshold values of water quality criteria (WQC) for other transition metals for which insufficient information on toxic potency i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…The sorption capacity is usually influenced by the ions’ properties, such as ionic radii, hydrated radius, atomic weight, electronegativity, and others, as already observed in other studies [ 42 , 43 , 44 , 45 ]. In this study, the ionic radius (Pauling) (Co 0.745 Å, Zn 0.74 Å, Cu 0.73 Å, and Ni 0.69 Å) and hydrated ionic radius (Zn 4.30 Å, Co 4.23 Å, Cu 4.19 Å, and Ni 4.04 Å) [ 46 ] represent the influence parameters.…”
Section: Resultsmentioning
confidence: 68%
“…The sorption capacity is usually influenced by the ions’ properties, such as ionic radii, hydrated radius, atomic weight, electronegativity, and others, as already observed in other studies [ 42 , 43 , 44 , 45 ]. In this study, the ionic radius (Pauling) (Co 0.745 Å, Zn 0.74 Å, Cu 0.73 Å, and Ni 0.69 Å) and hydrated ionic radius (Zn 4.30 Å, Co 4.23 Å, Cu 4.19 Å, and Ni 4.04 Å) [ 46 ] represent the influence parameters.…”
Section: Resultsmentioning
confidence: 68%
“…The electronegativity was considered to be important according to the MSE increase and the node purity increase. However, electronegativity was not found to be the main factor in the toxicity models since its P value exceeds 0.1, meaning that its importance was not statistically significant (Figure C), which is consistent with our previous study . Moreover, combining different indicators together overcomes the biases caused by a single indicator and identifies that the physicochemical properties of MNMs and the exposure conditions are both important for the toxicity assessment.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, it would be helpful to gain a better understanding of the influence of nano-TiO 2 on the toxicity of heavy metals from a quantitative structure-activity relationship (QSARs) viewpoint. The relationships between the characteristics of metal ions and their biological toxicity have already been confirmed by the use of QSARs (Wang et al, 2016;Wu et al, 2013). Ochiai et al (Ochiai, 1995) found that the toxicity mechanism of metals is closely related to the electronic structure of metal ions and their binding with biological macromolecular ligands.…”
Section: Introductionmentioning
confidence: 88%